Youth strengths arise from the ashes of adversity. Issue 3 (3rd July 2019) - Lind, Candace; Walsh, Christine; McCaffrey, Graham; Wardle, Mary-Lynn; Johansson, Bjorn; Juby, Brenda
ABSTRACT: With problem-oriented approaches to practice, policy and research, youth considered to be 'at-risk' are not often viewed from a strengths-based perspective. Explorations of youths' strengths are critical to help create environments where youth can flourish. The purpose of this research was to explore the resilience, healthy capabilities and strengths of youth at risk; from youth and staff perspectives across three community-based organizations in Western Canada. Through 17 interviews analyzed using hermeneutics, and further interpretation using metaphor development, stories arose of a journey progressing from loss and despair to fostering hope. The importance of youth having a voice and being included in decision-making was both a strength and a way of building strengths in youth. Multiple-level recommendations to help mediate the challenges and systems failures identified in these youths' journeys were identified; with an end goal of creating healthier futures for youth and a society in which they feel they belong.